Foreign Employment and Remittance in Nepal - Malla, Pushpa Shrestha (Economic Journal of Nepal, 2011)
This paper reviews the trend of foreign employment and remittances in Nepal. Nepalese migrants used to leave the country for foreign employment with various motives long back ago. The demand for Nepalese labor abroad has relieved the unemployment problem to some extent and the remitted fund has contributed to reduce the poverty level of the country to a larger extent. Among the various uses of remitted fund vary by reducing poverty, creating economic security and enhancing social status within the household and the community. Remittances have been playing pivotal role by relaxing foreign exchange constraint, increasing contribution to GDP and strengthening the balance of payment situation of the country. Various policy measures have been undertaken by the concerned authorities for encouraging remittances through official channels and use of the assets and skills of the returnees for themselves as well as for the economic development of the mutiny. Recent global economic crisis has compelled the concerned authorities to revise policies and programs regarding foreign employment regime of the country. Key words: Foreign employment; Remittance; Economic development Economic Journal of Nepal A Quarterly Publication of the Central Department of Economics T.U., Kirtipur Vol. 32, No. 1 January-March 2009, Issue No. 125 Page: 46-60 Uploaded date: 5 July 2011